The Antecendents Of Innovative Work Behavior: Concepts And Dimensions - Iffah Rosyiana; Intan Fauzi (P3I UMSurabaya, 2024)
The study aims of this article is to propose a definition, identify dimensions and concepts of innovative behavior in lecturers. Innovative work behavior means all lecturer behavior regarding ideas in general, promotion and implementation of new ideas, processes, products or procedures in the lecturer's work. The concept and definition of